2016
DOI: 10.1097/md.0000000000004842
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent spontaneous subserosal hematoma of ileum causing intestinal obstruction in a patient with menkes disease

Abstract: Background:Menkes disease (MD) is a disorder of copper metabolism due to ATP7A gene mutation that leads to severe copper deficiency. Deformed blood vessels can be found in many parts of the body, and intracranial hematoma is generally reported.Methods:We report a Taiwanese boy with MD who had recurrent spontaneous subserosal hematoma of ileum presenting as intestinal obstruction, with the 2 episodes 23 months apart. The patient returned to the usual physical status after surgical removal of the hematoma.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Recurrent spontaneous subserosal hemorrhage of the ileum was reported in a 3-year-old patient with MD and led to intestinal obstructions. [ 15 ] Belsha et al [ 9 ] described a multilobulated hyperplastic polyp with extensive involvement of the antrum and pylorus of the stomach in a 5-month-old patient with MD, and it caused marked upper gastrointestinal tract bleeding. A hyperplastic polyp of such a large size in infancy is extremely rare, and it was hypothesized that mucosal redundancy owing to LO deficiency in combination with chronic pressure during gastric peristalsis at the pyloric outlet predisposed the patient to polyp formation.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent spontaneous subserosal hemorrhage of the ileum was reported in a 3-year-old patient with MD and led to intestinal obstructions. [ 15 ] Belsha et al [ 9 ] described a multilobulated hyperplastic polyp with extensive involvement of the antrum and pylorus of the stomach in a 5-month-old patient with MD, and it caused marked upper gastrointestinal tract bleeding. A hyperplastic polyp of such a large size in infancy is extremely rare, and it was hypothesized that mucosal redundancy owing to LO deficiency in combination with chronic pressure during gastric peristalsis at the pyloric outlet predisposed the patient to polyp formation.…”
Section: Discussionmentioning
confidence: 99%
“…Weng et al reported a case of MD complicated with retroperitoneal hematoma (RPH), which is very rare in children. Spontaneous RH in children mostly occurs as a complication of other diseases ( 16 ).…”
Section: Review Of Causes Of Retroperitoneal Haemorrhagementioning
confidence: 99%